Inter perfectos christi – inter praefectos valentiniani. Służba publiczna i posługa biskupia Sydoniusza Apolinarego w świetle kolekcji listów - Skibiński, Tomasz (Vox Patrum, 2016)
Sidonius Apollinaris was a member of the Gallo-Roman aristocracy in the 5th century. His letters are a valuable source of information about many aspects of life in Gaul in the final period of the Roman Empire. The article presents the public service performed by Sidonius for nearly 20 years, which he then abandoned in favour of pastoral and Episcopal service, for a similar period of time. It aims to answer the question: what place did public service occupy in Sidonius’ life as a member of the Gallic aristocracy and what motivated him to take up an Episcopal ministry.